Análise de decisões relativas ao livramento condicional aplicado aos delitos de associação para o tráfico de drogas emanadas do STJ - CYPRIANO, Larissa do Amaral (2020)
The main objective of the present study is to analyze the content of contradictory decisions of the Brazilian Superior Court (Superior Tribunal de Justiça – STJ) related to the application of the conditional release benefit on crimes of association destinated to drug traffic. This analysis was determined this court, even though pacifying the understanding that this crime doesn’t have heinous nature, still applies the most severe quantum, intended for heinous crimes, for the application of conditional release. This reality denotes the presence of the enemy in criminal law, described in the theory of Günther Jakobs, criticized by Eugenio Zaffaroni. Therefore, this monography intents to examine these understandings by the methodology of decisions analysis, in order to identify the presence of the enemy figure in the decisions and if this reality is possible in a Democratic State.